Hmox1 (Heme Oxygenase-1) Protects Against Ischemia-Mediated Injury via Stabilization of HIF-1α (Hypoxia-Inducible Factor-1α). Issue 1 (January 2021) - Dunn, Louise L.; Kong, Stephanie M.Y.; Tumanov, Sergey; Chen, Weiyu; Cantley, James; Ayer, Anita; Maghzal, Ghassan J.; Midwinter, Robyn G.; Chan, Kim H.; Ng, Martin K.C.; Stocker, Roland
Abstract : Objective: Hmox1 (heme oxygenase-1) is a stress-induced enzyme that catalyzes the degradation of heme to carbon monoxide, iron, and biliverdin. Induction of Hmox1 and its products protect against cardiovascular disease, including ischemic injury. Hmox1 is also a downstream target of the transcription factor HIF-1α (hypoxia-inducible factor-1α), a key regulator of the body's response to hypoxia. However, the mechanisms by which Hmox1 confers protection against ischemia-mediated injury remain to be fully understood. Approach and Results: Hmox1 deficient ( Hmox1 –/– ) mice had impaired blood flow recovery with severe tissue necrosis and autoamputation following unilateral hindlimb ischemia. Autoamputation preceded the return of blood flow, and bone marrow transfer from littermate wild-type mice failed to prevent tissue injury and autoamputation. In wild-type mice, ischemia-induced expression of Hmox1 in skeletal muscle occurred before stabilization of HIF-1α. Moreover, HIF-1α stabilization and glucose utilization were impaired in Hmox1 –/– mice compared with wild-type mice. Experiments exposing dermal fibroblasts to hypoxia (1% O2 ) recapitulated these key findings. Metabolomics analyses indicated a failure of Hmox1 –/– mice to adapt cellular energy reprogramming in response to ischemia. Prolyl-4-hydroxylase inhibition stabilized HIF-1α in Hmox1 –/– fibroblasts and ischemic skeletal muscle, decreased tissue necrosis and autoamputation, and restored cellular metabolism to that of wild-type mice. Mechanistic studies showed that carbon monoxide stabilized HIF-1α in Hmox1 –/– fibroblasts in response to hypoxia. Conclusions: Our findings suggest that Hmox1 acts both downstream and upstream of HIF-1α, and that stabilization of HIF-1α contributes to Hmox1's protection against ischemic injury independent of neovascularization. Abstract : Supplemental Digital Content is available in the text.